Main temple atop the Harsha hill - Temples of India Project Team (Jio Institute, 2024)
The temple, now in a state of ruin consists of a mulaprasada of tri-anga specification, joined by a rangamandapa. It lacks the piṭha but starts from a single plinth course. The vedibandha is damaged in some places but otherwise had a kumbha with an intricate udgama motif and a small central box carrying a figure. The jangha, which is almost destroyed, once had dikpalas at the karṇas as evidenced by remains in the northeastern corner. The surasundaris likely adorned the pratirathas and the salilantara-recesses. Inside the sanctum is a shivalinga in active worship, likely contemporary with the main shrine. The temple lacks any super-structure which may have collapsed over the centuries. Stylistically the architecture of the Harshnath Temple falls in the Maha-Maru style but incorporates elements of the Maru-Gurjara style, particularly evident base mouldings and other temple features.